PAEDIATRIC SEPSIS STRATEGIES FOR EARLY DETECTION AND COLLABORATIVE CARE - DIN , N; AZMATULLAH , M; KHAN , M; ALI , H (Biological and Clinical Sciences Research Journal, 2024)
Paediatric sepsis remains a significant cause of mortality and morbidity globally, with a disproportionately high burden in low- and middle-income countries like Pakistan. The high rates of sepsis-related deaths in Pakistan are attributed to delayed diagnosis, inadequate healthcare infrastructure, antimicrobial resistance (AMR), and limited access to appropriate medical care. This review focuses on strategies for early detection and collaborative care approaches in the management of paediatric sepsis, particularly in the context of Pakistan’s healthcare system. Methods: This review synthesizes findings from recent studies (2014-2024) addressing the pathophysiology, risk factors, early detection strategies, and treatment modalities for paediatric sepsis, with an emphasis on the unique challenges faced in Pakistan. It discusses the role of biomarkers, clinical scoring systems, and multidisciplinary care models in improving outcomes for children with sepsis. The review also examines the impact of antimicrobial resistance on sepsis treatment and highlights technological advancements such as artificial intelligence and telemedicine that can aid in early diagnosis. Results: Early detection of paediatric sepsis in Pakistan is hindered by a lack of awareness, inadequate diagnostic tools, and delays in seeking medical care, particularly in rural areas. Biomarkers such as procalcitonin (PCT) and C-reactive protein (CRP) have shown promise in diagnosing sepsis, but their use is limited due to resource constraints. Collaborative care models, incorporating multidisciplinary teams and family-centred care, have improved outcomes in larger urban hospitals but remain underutilized in rural regions. Antimicrobial resistance presents a significant challenge, necessitating more stringent antibiotic stewardship programs. Conclusion: To reduce the burden of paediatric sepsis in Pakistan, efforts must focus on enhancing early detection through the implementation of standardized sepsis protocols, increasing access to diagnostic tools, and promoting collaborative care approaches. Addressing antimicrobial resistance through improved antibiotic stewardship is also critical. The integration of technological solutions, such as AI-based diagnostic tools and telemedicine, offers the potential for improving sepsis outcomes in resource-limited settings.